An Observational Study of Knowledge and Attitudes of Balanced Nutrition and Nutritional Status among High School Students in Bekasi City, Indonesia - Muh Nur Hasan Syah; Ika Wirya Wirawanti (Ikatan Sarjana Gizi Indonesia (ISAGI), 2021)
Nutrition problems in adolescents are influenced by various factors, one of the factors is the lack of promotion of balanced nutrition guidelines application. The application of balanced nutrition guidelines is influenced by knowledge and attitudes about the message of balanced nutrition guidelines. This study aimed to determine the relationship between knowledge and attitudes of balanced nutrition with nutritional status among adolescents. The type of this study was quantitative with a cross-sectional design, and the respondents were students of SMAN 1 Bekasi (16-18 years old). The independent variables of this study were knowledge and attitudes about balanced nutrition, and the dependent variable was nutritional status. The data were collected using a questionnaire about knowledge and attitudes of balanced nutrition and analyzed using the Fisher test. The results showed that there was a relationship between knowledge about balanced nutrition with nutritional status among adolescents in SMAN 1 Bekasi with a p-value of 0,040 (p <0,05), and also there was a relationship between the attitudes about balanced nutrition with nutritional status among adolescents in SMAN 1 Bekasi with p-value 0,002 (p<0,05). The conclusion was there was a relationship between knowledge and attitudes of balanced nutrition with nutritional status among adolescents in SMAN 1 Bekasi.